Tensiometer-Based Irrigation Management of Subirrigated Soilless Tomato: Effects of Substrate Matric Potential Control on Crop Performance - Montesano, Francesco F.; Serio, Francesco; Mininni, Carlo; Signore, Angelo; Parente, Angelo; Santamaria, Pietro (Frontiers in Plant Science, 2015)
This study aimed to determine the effects of irrigation management based on matric potential control on growth, plant-water relations, yield, fruit quality traits and water-use efficiency of subirrigated (through bench system) soilless tomato. Tensiometers were used for automatic irrigation control. Two cultivars, ‘Kabiria’ (cocktail type) and ‘Diana’ (intermediate type), and substrate water potential set-points (-30 and -60 hPa, for ‘Diana’, and -30, -60 and -90 hPa for ‘Kabiria’), were compared. Compared with -30 hPa, water stress (corresponding to a -60 hPa irrigation set-point) reduced water consumption (14%), leaf area (18%), specific leaf area (19%), total yield (10%) and mean fruit weight (13%), irrespective of the cultivars. At -60 hPa, leaf-water status of plants, irrespective of the cultivars, showed an osmotic adjustment corresponding to a 9% average osmotic potential decrease. Total yield, mean fruit weight, plant water and osmotic potential decreased linearly when -30, -60 and -90 hPa irrigation set-points were used in ‘Kabiria’. Unmarketable yield in ‘Diana’ increased when water stress was imposed (187 vs 349 g∙plant-1, respectively, at -30 and -60 hPa), while the opposite effect was observed in ‘Kabiria’, where marketable yield loss decreased linearly [by 1.05 g∙plant-1 per unit of substrate water potential (in the tested range from -30 to -90 hPa)]. Whereas in the second cluster, fruit total soluble solids and dry matter increased irrespective of the cultivars, in the seventh cluster in ‘Diana’ only a slight increase was observed from -30 vs. -60 hPa (3.3% and 1.3%, respectively, for TSS and dry matter), while in ‘Kabiria’ the increase was more pronounced (8.7% and 12.0%, respectively, for TSS and dry matter), and further reduction in matric potential from -60 to -90 hPa confirmed the linear increase for both parameters. Both glucose and fructose increased linearly in ‘Kabiria’ fruits on decreasing the matric potential, while in ‘Diana’ there was no increase. Control of substrate water status offer the possibility to steer crop response by enhancing different crop-performance components, namely yield and fruit quality, in subirrigated tomato. Small-size fruit varieties benefit more from controlled water stress in terms of reduced unmarketable yield loss and fruit quality improvements.